Composite bottom panel slamming of a fast planing hull via tightly coupled fluid-structure interaction simulations and sea trials. (1st October 2017) - Volpi, S.; Diez, M.; Sadat-Hosseini, H.; Kim, D.-H.; Stern, F.; Thodal, R.S.; Grenestedt, J.L.
Abstract: The paper presents partitioned tightly coupled fluid-structure interaction (FSI) simulations for composite panel slamming of a high-speed planing hull, including comparison with full-scale experiments. Panels with different layout/stiffness are investigated. Computational fluid dynamics (CFD) is performed using the URANS code CFDShip-Iowa. Computational structural dynamics (CSD) uses modal expansion by ANSYS finite elements. One- and two-way tightly coupled FSI is performed. The complexity of sea-trial conditions is reduced by statistical/frequency analysis, allowing for a simplified representation by one regular wave. Simulations provide details of slamming, including correlation of re-entering pressure peaks with motions and strain peaks. Numerical/modeling issues are discussed. Expected value and associated uncertainty of experimental pressure/strain peak and duration are used for validation. The difference of panels' dynamics is well predicted. Validation errors and uncertainties (average 25% and 14%) are quite large. Nevertheless, errors always fall within one standard deviation of experimental-data individual readings. Results are promising especially if compared to earlier slamming studies for regular/irregular waves in controlled towing tank tests, which show average error and validation uncertainty of 25% and 10%. The current study lays the groundwork for research on high-fidelity CFD/CSD FSI of real-world geometry slamming and ultimately multidisciplinary design optimization of structural and hull-form parameters. Highlights: A high-speed planing hull with composite bottom panels is studied. Two-way tightly coupled FSI simulations are performed in head and following waves. Regular wave simulations are compared to sea trials. Effects of composite material layout are investigated. Effects of one- versus two-way coupling on pressure and strain are discussed.